Challenges in personalised management of chronic diseases—heart failure as prominent example to advance the care process. Issue 1 (December 2015) - Brunner-La Rocca, Hans-Peter; Fleischhacker, Lutz; Golubnitschaja, Olga; Heemskerk, Frank; Helms, Thomas; Hoedemakers, Thom; Allianses, Sandra; Jaarsma, Tiny; Kinkorova, Judita; Ramaekers, Jan; Ruff, Peter; Schnur, Ivana; et al.
Abstract Chronic diseases are the leading causes of morbidity and mortality in Europe, accounting for more than 2/3 of all death causes and 75 % of the healthcare costs. Heart failure is one of the most prominent, prevalent and complex chronic conditions and is accompanied with multiple other chronic diseases. The current approach to care has important shortcomings with respect to diagnosis, treatment and care processes. A critical aspect of this situation is that interaction between stakeholders is limited and chronic diseases are usually addressed in isolation. Health care in Western countries requires an innovative approach to address chronic diseases to provide sustainability of care and to limit the excessive costs that may threaten the current systems. The increasing prevalence of chronic diseases combined with their enormous economic impact and the increasing shortage of healthcare providers are among the most critical threats. Attempts to solve these problems have failed, and future limitations in financial resources will result in much lower quality of care. Thus, changing the approach to care for chronic diseases is of utmost social importance.